Gait patterns of chronic ambulatory hemiplegic elderly compared with normal Age-Matched elderly - Kim, Junho; Oh, Se-In; Cho, Hyungpil; Kim, Hee Sang; Chon, Jinmann; Lee, Won Jae; Shin, Joon Ho; Ahn, Jae Yong; Kim, Taikon; Han, Jung-Soo; Jang, Hye-Youn; Han, Chang-Soo; et al. (International journal of precision engineering and manufacturing, 2015)
This study compares the gait of chronic ambulatory hemiplegic elderly (HE) with those of non-hemiplegic elderly (NHE) using Vicon® 512 motion analysis system to track movement trajectories. Subjects walked with self-selected gait speeds while temporal, spatial, and kinematic variables were analyzed. HE showed significantly decreased walking speed, cadence, stride length, and step length, and increased stride time, step time, and double limb support periods in comparison with NHE. Double limb support of stance phase was significantly increased in HE. In HE, affected pelvis showed marked upward elevation from terminal stance to mid swing phase, and greater external rotation than the NHE (p<0.05). Affected hip showed increased external rotation than the NHE. Affected knee showed loss of first and second flexion waves in sagittal plane. Affected ankle also showed reduced first rocker, and outward foot progression angle compared to NHE. Our results suggest that the major coping mechanism of HE to maintain balance and to continue walking is to increase the stance time of affected limb inevitably sacrificing walking speed. This study points to the importance and necessity of building a rehabilitation program that decrease the double limb support of affected limb while maintaining gait speed in the HE.